Effects of the Problem Solving Technique in Type 2 Diabetic Patients with Cognitive Impairment: A Randomized Clinical Trial - Camellia Torabizadeh; Katayoun Jalali; Marzieh Moattari; Hossein Moravej (Shiraz University of Medical Sciences, 2018)
Background: Diabetes mellitus is a common metabolic disorder, one of the lesser known of whose consequences is cognitive disorder. This study aimed to evaluate the effects of problem-solving technique in type 2 diabetic patients with cognitive impairment. Methods: This randomized clinical trial was conducted in the south of Iran between December 2014 and April 2015. 96 type 2 diabetic patients with cognitive impairment were randomly divided into two groups. The patients in the intervention group attended classes on problem-solving skills, while the patients in the control group attended the usual classes in the clinic. The quality of life, self-management profile, metabolic indexes of the patients in both groups were measured before and three months after the experiment. Data were analyzed using SPSS version 16.0. Paired t-test, independent t-test, Wilcoxon, Mann-Whitney and Chi-Square tests were used. Results: The differences between the groups' levels of HbA1c (P=0.02) and HDL (P=0.02) were significant, but the differences between their FBS, cholesterol, triglycerides and LDL were not significant (P>0.05). The mean difference of the changes in the quality of life (P<0.001) between the intervention and control groups was significant. The differences between the two groups in the area of self-management were as follows: patient's anxiety management (P<0.001), patient's capability in using medicine (P<0.001), healthy eating (P<0.001), weight management (P=0.02), and confidence in one's ability to manage his/her diabetes (P<0.001). Conclusion: Applying problem-solving technique significantly enhanced self-management, quality of life and metabolic indexes in type 2 diabetic patients with cognitive impairment. Trial Registration Number: IRCT2014041517283N1